Are land values related to ambient air pollution levels? Hedonic evidence from Mexico City. (6th February 2019) - Chakraborti, Lopamudra; Heres, David; Hernandez, Danae
Abstract: This article investigates whether residents of Mexico City value air quality. Our results suggest that air quality improvement in PM10 is equivalent to a marginal willingness to pay (MWTP) of US$440.31 per property for the period 2006–2013. The corresponding MWTP for PM2.5 is US$880.63, for O3 is US$623.78, and for SO2 is as much as US$2091.50. These estimates are considerably larger in magnitude compared to the few other studies in similar settings. As a percentage of annual household income, these represent 2.44 per cent for PM10, 4.88 per cent for PM2.5, 3.46 per cent for O3 and 11.59 per cent for SO2 . Our estimates of land value–pollution elasticities for PM10 (−0.26 and − 0.58) are within range of hedonic estimates for total suspended particulate matter in US cities around the 1970s. The corresponding elasticities range from − 0.55 to − 0.84 for PM2.5, from − 0.06 to − 0.49 for O3 and from − 0.11 to − 0.34 for SO2 .